Inverse problems in engineering mechanics III : International Symposium on Inverse Problems in Engneering Mechanics 2001 (ISIP 2001), Nagano, Japan /: International Symposium on Inverse Problems in Engneering Mechanics 2001 (ISIP 2001), Nagano, Japan. (2001) - Unknown
No abstract available